2019
DOI: 10.1088/2399-6528/ab4be6
|View full text |Cite
|
Sign up to set email alerts
|

A combined deep inelastic neutron scattering and ab initio lattice dynamics study of the hydride anion dynamics and bonding in La2LiHO3 oxyhydride

Abstract: Kobayashi et al (6279) (Science 2016, 351) reported recently the existence of pure Hconductivity in the oxyhydride La 2−x−y Sr x+y LiH 1−x+y O 3−y , while demonstrating its functionality through a prototype solid-state Ti/La 2 LiHO 3 /TiH 2 battery. In this study, we probe the atomistic motion of La 2 LiHO 3 obtained by the promising halide salt flux method, via a combination of deep inelastic neutron scattering (DINS) and ab initio lattice dynamics (LD) calculations verified by vibrational inelastic neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Either way, because half of all planar anion sites in LLHO are occupied by O atoms [Figure a], high-energy V O species must be involved in hydride diffusion. The high associated energy barriers will limit ionic conductivity, as previous studies have observed. , …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Either way, because half of all planar anion sites in LLHO are occupied by O atoms [Figure a], high-energy V O species must be involved in hydride diffusion. The high associated energy barriers will limit ionic conductivity, as previous studies have observed. , …”
Section: Discussionmentioning
confidence: 86%
“…The high associated energy barriers will limit ionic conductivity, as previous studies have observed. 21,36 SLHO, in contrast to LLHO, has a favorable structure for hydride conduction because all of the planar octahedral sites are occupied by H and the migration barrier for V H + is low. As outlined in Figure 3, O H − serves as a compensating acceptor for three different species depending on chemical potential: for very O-poor conditions, H O + , and at higher oxygen chemical potentials either V H + or H i + , depending on the hydrogen chemical potential.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The complex in question is particularly suited to this technique as the deuteration process serves to provide a contrast measurement, allowing direct experimental distinction of modes belonging to the Cp* subunit. INS was therefore used to obtain a complete set of vibrational bands for both H 15 Cp*Rh–Cl and D 15 Cp*Rh–Cl which were then assigned using density functional theory phonon calculations. DFT methods are well established in studies of the reactivity of metal complexes and metalloenzymes. , Validation of a particular DFT model through comparison to INS results has an added layer of rigor as it validates the local energy landscape of the model within the harmonic approximation. These validated DFT models then allowed us to demonstrate for the first time that vibrational energies and the motions of individual atoms can play crucial roles in the overall reaction profile for methyl activation.…”
mentioning
confidence: 99%
“…Additionally, Fjellvåg et al 15 have studied the La 2 LiHO 3 member of that series and found hydride mobility within the perovskite layer to be more facile than in the rock salt layer, which they link to La-O covalency, and that vacancies promote hydride diffusion. 16 In 2019 Takeiri et al 17 reported the high-pressure synthesis of Ba 2 ScHO 3 and observed hydride conduction at 300 • C. This compound also adopts the n = 1 RP structure but differs from previous examples in that the hydrides are distributed over the "apical" points of the octahedra and so reside in the rock salt layer, as indicated in Figure 1(d). This difference can be explained by straightforward electrostatic considerations, whereby the most positively charged cations coordinate to the most negatively charged cations.…”
Section: Introductionmentioning
confidence: 95%